Cells, walls, and endless forms. (December 2016) - Monniaux, Marie; Hay, Angela
Highlights: Conserved genes control diverse cellular adaptations for life on dry land. Diverse cuticle and secondary cell wall patterns underpin novel plant functions. Oriented cellular growth and localized growth repression shape diversity of form. Abstract : A key question in biology is how the endless diversity of forms found in nature evolved. Understanding the cellular basis of this diversity has been aided by advances in non-model experimental systems, quantitative image analysis tools, and modeling approaches. Recent work in plants highlights the importance of cell wall and cuticle modifications for the emergence of diverse forms and functions. For example, explosive seed dispersal in Cardamine hirsuta depends on the asymmetric localization of lignified cell wall thickenings in the fruit valve. Similarly, the iridescence of Hibiscus trionum petals relies on regular striations formed by cuticular folds. Moreover, NAC transcription factors regulate the differentiation of lignified xylem vessels but also the water-conducting cells of moss that lack a lignified secondary cell wall, pointing to the origin of vascular systems. Other novel forms are associated with modified cell growth patterns, including oriented cell expansion or division, found in the long petal spurs of Aquilegia flowers, and the Sarracenia purpurea pitcher leaf, respectively. Another good example is the regulation of dissected leaf shape in C. hirsuta via local growth repression, controlled by the REDUCED COMPLEXITY HD-ZIP class I transcription factor. These studies in non-model species often reveal as much about fundamental processes of development as they do about the evolution of form.